RESOLUSI KONFLIK DI ASIA: ANALISIS PERBANDINGAN ACEH DAN SRI LANGKA - Putri Marzaniar (Al-Ijtima`i: International Journal of Government and Social Science, 2022)
The conflicts in Aceh and Sri Lanka share many similarities. However, there have been significantly different post-tsunami dynamics of conflict resolution in Aceh and Sri Lanka. In this article, the conflict resolution processes in Aceh and Sri Lanka will be compared. The main goals of this article are to (1) identify the main factors that failed to resolve the Sri Lanka conflict and the main factors that contributed to the successful post-tsunami resolution of the Aceh conflict, and (2) to determine whether the Sri Lanka conflict's failure to be resolved will repeat in Aceh if Aceh is faced with a similar natural disaster (tsunami). This article uses a qualitative approach with multiple case studies. As a result, the author uses a scientific model that includes additional concepts, expert opinions, and theories about conflict resolution to comprehend and analyze the resolution of the Aceh conflict and the conflict in Sri Lanka. These findings demonstrate that the success or failure of post-disaster resolution in two areas depends critically on the level of trust between conflicting parties. As a reaction, the violations of the Helsinki Accords' terms are more likely to trigger a third wave of conflicts than future natural disasters In Aceh.